2021
DOI: 10.1080/18335330.2021.1906932
|View full text |Cite
|
Sign up to set email alerts
|

The use of family networks in suicide terrorism: a case study of the 2018 Surabaya attacks

Abstract: This article investigates the use of family networks in suicide terrorism using the 2018 Surabaya suicide attacks as a case study. The Surabaya attacks were the first case in the region that involved entire family networks including parents and their young children. The main aim of the article is to provide an understanding of the use of family networks in suicide terrorism particularly that of women and children and explore the implications that it has for the region. It is argued that there are numerous adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Doosje et al (2016) define radicalization as a process where people motivate to use violence toward other groups that are targeted to create a behavioral change and reach political goals. Many studies have found that family influences an individual to join radical groups, which can be divided into internal or external factors (Barricman 2019;Bloom 2010Bloom , 2011Curtis 2020;Dass 2021;Doosje et al 2016;Gitaningrum 2021;Jadoon 2020;Kasanah;Kurniati 2021;Musfia 2017;Rasyid 2018;Rozika 2017;Sikkens et al 2017;Wickham et al 2019;Vergani et al 2018;Zuhdi & Syauqillah 2019). However, there are few studies that analyze the role of the family in the deradicalization of terror convicts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doosje et al (2016) define radicalization as a process where people motivate to use violence toward other groups that are targeted to create a behavioral change and reach political goals. Many studies have found that family influences an individual to join radical groups, which can be divided into internal or external factors (Barricman 2019;Bloom 2010Bloom , 2011Curtis 2020;Dass 2021;Doosje et al 2016;Gitaningrum 2021;Jadoon 2020;Kasanah;Kurniati 2021;Musfia 2017;Rasyid 2018;Rozika 2017;Sikkens et al 2017;Wickham et al 2019;Vergani et al 2018;Zuhdi & Syauqillah 2019). However, there are few studies that analyze the role of the family in the deradicalization of terror convicts.…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, the Surabaya case in 2018 was a big blow for Indonesia because it showed the development of an extreme action involving all family members carrying out suicide bombings. In Dass's (2021) study, this is due to two reasons: first, it shows a new trend in terrorism where perpetrators are motivated mainly by a misinterpreted religious ideology as compared to most of the previous suicide terrorism cases where attackers were motivated by nationalistic and liberation ideologies from foreign occupying forces. Second, it is the first case in the region involving the use of the entire family including parents to arm their own young children.…”
Section: Findings and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The suicide bombing case carried out by Dita and his family was a wrong action because it sacrificed many innocent people. The case of the suicide bombing in Surabaya shows that individuals may be motivated and initiated to carry out suicide attacks primarily by a misconstrued religious ideology or belief rather than motivations that are nationalistic (Santhana Dass, 2021).…”
Section: The Analysis Of Terrorist Religiosity Based On Psychographic...mentioning
confidence: 99%